Evaluation of the leaching characteristics of low-grade nickel laterite waste rock for indirect carbon sequestration application - Eusebio, Ramon Christian P. (Animo Repository, 2020)
The potential utilization of waste rock obtained from an active nickel mine site in Mindanao, the Philippines for indirect carbon sequestration is explored in this study. X-ray diffraction (XRD), X-ray fluorescence (XRF), and inductively coupled plasma optical emission spectroscopy (ICP-OES) results showed that the sample is rich in iron, existing in three different forms: goethite (α-FeOOH), chromite (FeCr2O4), and magnetite (Fe3O4). Leaching tests performed using hydrochloric acid (HCl) showed high iron extraction rates, with a maximum average extraction efficiency of 95.35% obtained at 100°C, 4 M HCl, and 1.0 h. Morphological and physicochemical analyses conducted through scanning electron microscopy and Brunauer–Emmett–Teller (BET) method supported the high extraction rates obtained for Fe, which is due to the higher reactivity of the sample to the leaching agent as well as the higher availability of accessible sites for reaction on the sample surface as compared to other mine wastes that are previously utilized. The nickel laterite waste rock sample has the potential to be used as a feedstock for iron carbonation in indirect carbon sequestration; however, challenges such as the use of sulfide source and cost requirements must be addressed in order to fully determine its viability for industrial scale application. © 2020 The Korean Society of Mineral and Energy Resources Engineers (KSMER).